(untitled) (Al-Qamar, 2022)
This article is discussing about Prevention of the social imbalances in the light of Seerat-e-Taybah (Holy Prophet Peace Be Upon Him). It also has been discussed before the advent of Islam. After this it commences in the eradication of extremism and rigidity in the light of Seerat-e-Taybah. It also through light politically consolidated society, more over it tells us Islam is the religion of universal brotherhood and free of prejudice and also tells us how we can make economical strong society and how can we formulate terrorism free society. Finally, this article is concluded with suggestion and recommendation gist of discussion. Before the study of the teachings of the Holy Prophet it is important to present a brief comparative analysis of the pre-Islam existing nations’ narrow mindedness. In present scenario it seems pre-Islamic atmosphere is reviving again. Before Islam different nations were demonstrating narrow mindedness. We are witnessing the same situation again. Before Islam narrow mindedness of society is narrated by Allama Fareed Wajdi as, people were forced to accept religion and cruelty was very common, the people who refused to accept religion were put in fire and they were thrown before wild animals, and their legs were tied with the legs of horses and they were dragged into different directions. Melting mettle was thrown to them or they were hung on light fire for many days without caring for their noise or shout. They were made to lie on bed of hot coal which cased blood and fat come out of this body and some time they were lynched to death. When we study the pure life of the Holy Prophet “Seerat Tyaba” and Islamic society as compared to extremism and narrow mindedness and when we see the moderation, then Islamic moderation and optimism reflects with full force and glow. Neither its examples could be witnessed before Islam nor after Islam. The teachings of the Holy Prophets and his practices which completely pure from narrow mindedness, due to its effect the Arabs Shepherds who were used to implicit humanity turned to be complete human.